Pozzolanicity of finely ground lightweight aggregates. (April 2018) - Suraneni, Prannoy; Fu, Tengfei; Jafari Azad, Vahid; Isgor, O. Burkan; Weiss, Jason
Abstract: This paper examines the pozzolanic behavior of finely ground lightweight aggregates with a mean particle size between 4 and 26 μm. Cement pastes are made with a 20% mass replacement of cement with finely ground lightweight aggregates, fly ash, quartz, and limestone in addition to a control paste with no cement replacement. Isothermal calorimetry, thermogravimetric analysis, and compressive strength testing as well as thermodynamic calculations are performed on these pastes. Isothermal calorimetry and compressive strength testing are shown to not be able to clearly distinguish and quantify the pozzolanic response of the finely ground lightweight aggregates, fly ash, quartz, and limestone when they are used in cement pastes. However, thermogravimetric analysis and thermodynamic calculations clearly show that the finely ground lightweight aggregates are pozzolanic through the consumption of calcium hydroxide. A pozzolanic reactivity test based on isothermal calorimetry also confirms that the finely ground lightweight aggregates are pozzolanic. These results indicate that finely ground lightweight aggregates are pozzolanic and could be used in concreting applications.